Synthesis of carbon nanotubes and its potential application in protein purification by using skim latex serum - N,M, Mubarak; Yusof, Faridah; Al-Khatib, Ma'an Fahmi Rashid; Al Hazza, Muataz Hazza Faizi; I.Y, Qudsieh; Al-Saadi, Mohammed A.; Mohamed, Khalid (2009)
Carbon nanotubes (CNTs) have been synthesized by a gas phase double stage chemical vapor deposition (DS-CVD) technique using acetylene (C2H2) and hydrogen (H2) as precursor gases. The morphology and the structure of CNTs were characterized using field emission scanning electron microscope (FSEM) and transmission electron microscope (TEM). The CNTs produced were purified and functionalized by using covalent functionalization methods. The functionalized CNTs were used as column chromatographic media for skim latex protein purification. In this process, pH and ionic strength were optimized to achieve higher efficiency in protein purification. ©2009 American Institute of Physics